The Effect of Instructional Strategies and Learning Motivation on Learning Outcomes of Sciences - Umi Fatonah , Zulfiati Syahrial , Priyono , Jarudin (International Journal of Advanced Science and Technology, 2020)
This study aims to obtain a picture of the effect of guided instructional strategies inquiry andinteractive expository strategies (external factors) as well as high and low learning motivation(internal factors) on the learning outcomes of Sciences. This study uses a treatment design on a2x2 treatment by level design consisting of instructional strategies (A) and learning motivation(B). Instructional strategies (A) consist of groups that are treated guided inquiry strategies (A1)as an experimental class, and interactive expository strategies (A2) as a control class. Whilelearning motivation (B) consists of two groups, namely the high learning motivation group (B1)and the low learning motivation group (B2). The design of the treatment in research is theinstructional strategy that will be given to students in the learning process in class. Effect of AllIndependent Variables (Strategy, Motivation and Strategy Interaction with Motivation or"Strategy * Motivation") together on the dependent variable (Science Learning Outcomes).Because Significance (Sig.) .000 <0.05 (α) Significant means that the model is valid, it can beconcluded that the variable has an interaction. The results of instructional strategies of learningmotivation have a significant effect on learning outcomes of Sciences. The conclusion is that theguided inquiry strategy and learning motivation can improve learning outcomes